Filoksen z Mabbug, O tym, jak przyjmować Komunię Świętą na rękę - Szymczak, Tomasz (Vox Patrum, 2024)
Translation into Polish of Philoxenus of Mabbu's work On Gestures and Prayer When One Recieves Communion in the Hand.